PENGARUH PENERAPAN GOOD GOVERNANCE, PENGENDALIAN AKUNTANSI, DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DESA DALAM PENGELOLAAN DANA DESA SE-KECAMATAN TANON KABUAPTEN SRAGEN - Lia Amelia; Muhammad Hasan Ma’ruf; Suprihati Suprihati (CV. Denasya Smart Publisher, 2025)
This research aims to analyze the influence of the application of good governance, accounting controls, and reporting systems on the performance accountability of village government agencies in the management of village funds throughout the Tanon Sub-district. This type of research is quantitative with a survey approach and data collection techniques through questionnaires. The population in this study comprises all village officials in the Tanon District of Sragen Regency, with a sample size of 80 respondents taken using the saturated sampling method. Data analysis techniques include descriptive statistical tests, validity tests, reliability tests, and classical assumption tests. For hypothesis testing, multiple linear regression tests, t-tests, F-tests, and coefficient of determination tests were used. The results of the study indicate that the implementation of good governance has a positive impact on the accountability of village government performance. Accounting control does not positively impact the accountability of government performance. Reporting systems do not positively impact the accountability of village government performance.